La famille McCord : une vision passionnée = The McCord family : a passionate vision - Miller, Pamela, 1944- (Musée McCord d'histoire canadienne, 1992)
In 1921 David Ross McCord (1844-1930) founded the McCord Museum of Canadian History, which first opened in the Jessie Joseph House of McGill University. McCord's ancestors had come from Ireland to settle in Canada after the Seven Years War. Although they were initially merchants, by the late eighteenth and early nineteenth centuries the McCords derived most of their wealth from the management of seigneurial land and from the subdivision of Temple Grove, their mountain estate which covered the area now bounded by Côte des Neiges Road and Cedar Avenue. This record of the McCords and their interest in religion, education and science reflect the intellectual trends of the era. David Ross McCord sought to collect in the broadest and most objective manner, and his pursuit of his dream to create a national museum of Canadian history provides valuable insight into the evolution of Montreal.